The Yin and Yang of the Bone Marrow Microenvironment: Pros and Cons of Mesenchymal Stromal Cells in Acute Myeloid Leukemia - Ciciarello, Marilena; Corradi, Giulia; Loscocco, Federica; Visani, Giuseppe; Monaco, Federica; Cavo, Michele; Curti, Antonio; Isidori, Alessandro (Frontiers in Oncology, 2019)
Mesenchymal stromal cells (MSCs) have, for a long time, been recognized as pivotal contributors in the setup and maintenance of the hematopoietic stem cell (HSC) niche, as well as in the development and differentiation of the lympho-hematopoietic system. MSCs also have a unique immunomodulatory capacity, which makes them able to affect, both in vitro and in vivo, the function of immune cells. These features, namely the facilitation of stem cell engraftment and the inhibition of lymphocyte responses, have both proven essential for successful allogeneic stem cell transplantation (allo-SCT), which remains the only curative option for several hematologic malignancies. For example, in steroid-refractory acute graft-versus-host disease developing after allo-SCT, MSCs have produced significant results and are now considered a treatment option. However, more recently, the other side of the MSC coin has been unveiled, because of their emerging role in creating a protective and immune-tolerant microenvironment able to support the survival of leukemic cells and affect the response to therapies. In this light, it has been proposed that the failure of current treatments to efficiently override the stroma-mediated protection of leukemic cells accounts for the high rate of relapse in acute myeloid leukemia, at least in part. In this review, we will focus on emerging microenvironment-driven mechanisms conferring a survival advantage to leukemic cells overt physiological HSCs. This body of evidence increasingly highlights the opportunity to consider tumor-microenvironment interactions when designing new therapeutic strategies.